MICROBIAL LOADS OF PIGS FED SUNDRIED SOYBEAN MILK RESIDUE - Dr. Paramesh H (African Journal of Environmental Economics and Management, 2025)
Screening of raw pig manure collected from crossbred growing pigs fed sundried soybean milk residue were carried out at the piggery unit of the Oyo State College of Agriculture and Technology, Igboora, Nigeria. Eighteen (18) crossbred (Largewhite X Landrace) obtained from piggery unit of Oyo State College of Agriculture and Technology, Igboora, Nigeria weaned pigs were used for the study and the experimental animals were allotted into three treatments with six animals per treatment and two animals per replicate. The experimental design used was completely randomized design, data collected were analyzed using one way analysis of variance of statistical system software. The microbiological assays of fresh faecal, total microbial count, lactobacillus, coliform, salmonella and saccharomyces were isolated from pig manure. The experiment lasted eight weeks. At the end of the experiment, bacteria and pro- tozoa counts were not significantly (p > 0.05) different. The highest count (3.61 x 10-9 cfu/ml) was obtained at T1 (control) and the lowest value (3.65 x 10-9 cfu/ml) were obtained in pigs fed 10% (T3) sundried soybean milk residue for total microbial count. Lacto- bacillus value ranged from (2.82 x 10-3 cfu/ml) to (2.85 x 10-3 cfu/ml).The highest value of coliform, salmonella and saccharomyces were recorded in pigs kept in the control diet (1.66 x 10-1, 1.38 x 10-1 and 2.14 x 10-2) respectively. It can be concluded that sundried soybean milk residue had no influence on the microbial load of pigs.